Bond-graph-based controller design for the quadruple-tank process. (2015) - Nacusse, Matías A.; Junco, Sergio J.
The quadruple-tank process has been proposed as a benchmark for multivariable control system design. This paper addresses the design in the bond-graph domain of a robust controller having the volumetric flows of two pumps as manipulated variables and the level of the two lower tanks as the regulated outputs. The basic control objectives are expressed in terms of desired closed-loop energy and power-dissipation functions and captured in the bond-graph domain by means of a so-called target bond-graph. A basic controller design performed via bond-graph prototyping yields a primary control law which is further robustified against parameter uncertainties, measurement deviations and faults using the diagnostic bond-graph concept. This results in an additional closed-loop consisting of a PI-law which is represented by a physically meaningful bond-graph subsystem. The design methodology is first developed on a simpler two-tank SISO-control problem and then straightforwardly extended to the multivariable problem with the help of some causal manipulations on the four-tank bond-graph model.